Na3[B20H17NH3]: synthesis and liposomal delivery to murine tumors. - Feakes, D A (1994)
The polyhedral borane ion [n-B20H18]2- reacts with liquid ammonia in the presence of a suitable base to produce an apical-equatorial (ae) isomer of the [B20H17NH3]3- ion, [1-(2'-B10H9)-2-NH3B10H8]3-. The structure of this product has been confirmed by 11B NMR spectroscopy and x-ray crystallography. This species undergoes acid-catalyzed rearrangement to an apical-apical (a2) isomer, [1-(1'-B10H9)-2-NH3B10H8]3-, whose structure has been determined by 11B NMR spectroscopy. The sodium salts of both the ae and the a2 isomers of [B20H17NH3]3- have been encapsulated within small unilamellar liposomes, composed of distearoyl phosphatidylcholine/cholesterol (1:1), and investigated as boron-delivery agents for boron neutron capture therapy (BNCT) of cancer. The biodistribution of boron was determined after the injection of liposomal suspensions into BALB/c mice bearing EMT6 tumors. Both [B20H17NH3]3- isomers exhibited excellent tumor uptake and selectivity at very low injected doses, achieving peak tumor boron concentrations of 30-40 micrograms of B/g of tissue and tumor/blood boron ratios of approximately 5. The enhanced retention of the [B20H17NH3]3- isomers by EMT6 tumors may be attributed to their facile intracellular oxidation to an extremely reactive NH3-substituted [n-B20H18]2- ion, the electrophilic [B20H17NH3]- ion. Both isomers of [B20H17NH3]3- are at least 0.5 V more easily oxidized than other previously investigated species containing 20 boron atoms. In another experiment, [ae-B20H17NH3]3- was encapsulated in liposomes prepared with 5% PEG-2000-distearoyl phosphatidylethanolamine in the liposome membrane. As expected, these liposomes exhibited a longer circulation lifetime in the biodistribution experiment, resulting in the continued accumulation of boron in the tumor over the entire 48-hr experiment and reaching a maximum of 47 micrograms of B/g of tumor.